Integrasi Perilaku Sosial Dalam Pembelajaran PJOK: Kajian Literatur - Givi Garsiva; Iis Marwan; Nanang Kusnadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The objective of this study is to summarize, compare, and interpret empirical evidence related to the integration of social behavior in Physical Education (PJOK) learning. The method used in this study is a narrative literature review with a multi-stage selection process following the PRISMA flow, identifying 100 articles from reputable databases such as Scopus, Taylor & Francis, SAGE Journals, and Google Scholar, filtered to include SINTA-indexed journals. After deduplication, title–abstract screening, and full-text assessment, a total of 30 articles met the inclusion criteria. The analysis was conducted using a thematic narrative synthesis by grouping studies based on similarities in concepts, objectives, intervention models, and social behavior outcomes, along with methodological analysis using quality indicators such as research design, sample size, appropriateness of affective instruments, and measurement reliability. The results of this study reveal four main themes: (1) the effectiveness of Cooperative Learning in developing students’ cooperation, communication, empathy, and responsibility; (2) the contribution of social values and the affective domain in shaping character and prosocial behavior; (3) the role of Social Emotional Learning (SEL) and emotion regulation interventions in strengthening students’ social behavior; and (4) the role of teachers and the school environment as determining factors in the successful integration of social behavior in PJOK learning. In conclusion, this study highlights the importance of strengthening teacher competencies, developing standardized affective assessment instruments, and the need for experimental and longitudinal research to address existing methodological gaps. Keywords: Cooperative Learning, Physical Education (PJOK), Social Behavior, Social Emotional Learning